2023
DOI: 10.3390/ijerph20032299
|View full text |Cite
|
Sign up to set email alerts
|

How Does COVID-19 Risk Perception Affect Sense of Control? The Roles of Death Anxiety and Confucian Coping

Abstract: This research examined the impact of COVID-19 risk perception on sense of control, testing the hypotheses that COVID-19 risk perception would reduce sense of control and that this effect would be mediated by death anxiety and moderated by Confucian coping. A series of six studies were conducted with Chinese participants (N = 2202) and employed different research designs in lab and real-life settings. Across the studies, we found that the perceived risk of COVID-19 impaired sense of control. Studies 3a to 5 fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Previous research has shown that risk perception was negatively associated with sense of mastery (Nordgren et al, 2007 ; Ruthig et al, 2007 ; Huang et al, 2023 ). When individuals perceive risks and threats in the environment, especially those beyond their control, it may lead to a decrease in their sense of mastery (Huang et al, 2023 ). The findings from the current study further support the important role of hope and sense of mastery in determining career adaptability among Chinese college students.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous research has shown that risk perception was negatively associated with sense of mastery (Nordgren et al, 2007 ; Ruthig et al, 2007 ; Huang et al, 2023 ). When individuals perceive risks and threats in the environment, especially those beyond their control, it may lead to a decrease in their sense of mastery (Huang et al, 2023 ). The findings from the current study further support the important role of hope and sense of mastery in determining career adaptability among Chinese college students.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, the current study showed that susceptibility was indirectly associated with career adaptability (including concern, confidence, control, and curiosity) through sense of mastery. Previous research shown that risk perception was negatively associated with sense of mastery (Nordgren et al, 2007;Ruthig et al, 2007;Huang et al, 2023). When individuals perceive risks and threats in the environment, especially those beyond their control, it may lead to a decrease in their sense of mastery (Huang et al, 2023).…”
Section: Risk Perception Of Covid-indirectly a Ects Career Adaptabili...mentioning
confidence: 96%
“…Peluso and Pichierri investigated the influence of socio-demographics on individuals' sense of control and the ability to avoid the uncertainty caused by the COVID-19 crisis [20]. Huang et al examined the impact of COVID-19 risk perception on the sense of control, testing the hypotheses that this effect would be mediated by anxiety about death and moderated by Confucian coping [21].…”
Section: Literature Reviewmentioning
confidence: 99%